2015
DOI: 10.1007/s13277-015-3341-2
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin B1 induces Src phosphorylation and stimulates lung cancer cell migration

Abstract: AflatoxinB1 (AFB1) is well known as a potent carcinogen. Epidemiological studies have shown an association between AFB1 exposure and lung cancer in humans. AFB1 can induce the mutations of genes such as tumor suppressor p53 through its metabolite AFB1-8,9-exo-epoxide, which acts as a mutagen to react with DNA. In addition, recent study demonstrates AFB1 positively regulates type I insulin-like growth factor receptor (IGF-IR) signaling in hepatoma cells. The current study aims to determine the effects of AFB1 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Longer-term studies of the effects of aflatoxins on mucociliary transport, potentially in an animal model of aflatoxin-exposure, will help to shed light on situations of chronic exposure and effects on airways. To our knowledge, studies of longer term exposures have only been previously done in airway cells 34 51 52 53 54 55 56 57 and animals 28 58 59 60 61 62 with a focus on carcinogenesis. The concentrations of aflatoxins used here (0.1–10 μM) are in the same range used in previous in vitro and ex vivo studies by other groups 4 52 53 56 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Longer-term studies of the effects of aflatoxins on mucociliary transport, potentially in an animal model of aflatoxin-exposure, will help to shed light on situations of chronic exposure and effects on airways. To our knowledge, studies of longer term exposures have only been previously done in airway cells 34 51 52 53 54 55 56 57 and animals 28 58 59 60 61 62 with a focus on carcinogenesis. The concentrations of aflatoxins used here (0.1–10 μM) are in the same range used in previous in vitro and ex vivo studies by other groups 4 52 53 56 57 .…”
Section: Discussionmentioning
confidence: 99%
“…In detail, Western blot analysis was to evaluate IRS expression and Src, Akt and ERK phosphorylation in lung cancer cell lines, A549 and SPCA-1, after AFB1 treatment. These studies showed that AFB1: (i) up-regulates IRS1 and IRS2; (ii) induces Src, Akt and ERK1/2 phosphorylation; (iii) stimulates lung cancer cell migration, which can be inhibited by saracatinib [ 71 ].…”
Section: Aflatoxins Related Diseasesmentioning
confidence: 99%
“…Liu and Wu [30] reported in their study that people with chronic hepatitis B infection and exposed to aflatoxin B1 have a high risk of developing liver cancer tenfold or more. Other studies have also highlighted the role of AFB1 in the development of other types of cancer such as kidney, respiratory and gastrointestinal cancer [31][32]. In addition to its carcinogenicity, AFB1 is an immunosuppressive compound, decreasing resistance to parasitic, bacterial and fungal infections.…”
Section: Discussionmentioning
confidence: 99%